Features of soils of the natural park “Scherbakovsky” Volgograd region - O. A. Gordienko; N. V. Onistratenko; D. A. Andreeva (Бюллетень Почвенного института им. В.В. Докучаева, 2023)
The paper presents the results of a study of the soil cover of the Shcherbakovsky Nature Park in the Kamyshinsky district of the Volgograd region. To achieve the results 12 soil sections were laid along the studied soil catena (1.5 km), so that morphological and chemical features of the soils of the study area were investigated. Variety and diversity are due to vertical zonality and geological and hydrological peculiarities. So, in the gullies and in massive forest plantations various dark humus and gley soils have become widespread. On steppe, slope and watershed areas lithosolic light humus luvisols and light humus lithozems were formed. On areas with open sand surface, humus psammozems with protohumus horizons W, as well as light humus (AJ-C) and humus soils (A-C), and a variety of soil-forming rocks of the natural park were found. In relief depressions they are represented mainly by gleyed sandy, as well as proluvial-deluvial deposits with inclusions of large fragments of opokas. On steppe and steep-slope areas, the soil-forming rocks are thick layers of opoka deposits. Their upper boundary varies from 20 to 60 cm depth depending on the meso- and microrelief. On the watersheds, the soilforming rocks are represented by sandy, ferruginous deposits with new formations of clay and pseudofibres. The parent rock is registered starting from 100 cm depth and consists of large blocks of hardened sandstone. The chemical properties of the studied soils are characterized by a neutral or slightly acidic pH. Easily soluble salts are leached from all soil horizons. The maximum values of Сorg are typical of humus and transitional horizons. The studies conducted in the Shcherbakovsky Nature Park are of greatest importance for monitoring the state of soils, and also allowed us to identify the features of the genesis of underdeveloped soils and luvisols of the dry-steppe natural zone.